Additional Techniques in Serous Effusions - A. G. J. M. Hanselaar (Analytical Cellular Pathology)
Cytological examination is a valuable diagnostic tool in case of a serous effusion. The firstmanifestation of malignancy may be an effusion of the pleural, pericardial, or peritoneal cavity, especially in carcinoma of the ovary, or lung, and malignant mesothelioma. In other malignancies effusions may occur in the course of the disease. The contribution by Motherby et al. in this issue of ACP focuses on the contribution of image and flow cytometry to establish the presence or absence of malignancy in serous effusions [16]. They point out that the sensitivity of DNA image cytometry in equivocal effusions may be as high as 87.5%, and that for the detection of malignancy, DNA image cytometry is superior to flow cytometry.